Love, Family and Friendship : a Latin American Perspective - Agnaldo, Garcia (Cambridge Scholars Publishing, 2014)
Love, Family and Friendship: A Latin American Perspective presents current research on different aspects of interpersonal relationships, including romantic and couple relations, family relationships and friendship, either conducted in Latin America or involving Latin American participants. The contributors to this volume are drawn from different universities in Brazil, Chile, Colombia, Mexico, Puerto Rico and USA. The chapters are based on papers presented at the First Latin American Meeting ...